Study Application Of Soil Conservation Techniques Along Highway Openings - Flaviano Fernandes (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
The objective of this research is to find out the methods used in soil conservation along the opening of the Tibar-Ermera highway and to find out the types of plants used in implementing soil conservation along the opening of the Tibar-Ermera highway. This research uses a descriptive or exploratory method referring to the method created by Vogel (1987) and Rugayah, et al (2004). This exploratory research will be carried out along the highway, to observe what soil conservation methods are used. Based on the results of observations along the opening of the highway, soil conservation techniques are applied along the Tibar-Gleno road, it is known that there are two methods, namely vegetative methods and mechanical methods or civil engineering methods. The vegetative method applied is planting vetiver grass, elephant grass, gamal and dadap hijo and the mechanical method is bench terraces and civil engineering methods are retaining walls and channels. And the types of plant species used in soil conservation include Vetiveria zizanioides L Nash, Pennisetum purpureum, Gliricidia maculate.